Ke-Hujjah-an Sadd Al-Dhari’ah - Ulin Na'mah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2015)
Sadd al-dhari>’ah is an effort of blocking a likely way that may end up in forbidden and destructive things. In other words, it is a way to ban something which is basically aloowed, resulted from its potency of bringing about doing something absolutely forbidden. Therefore, in this case, it is considered a method of legislating syar’i law, instead of whether or not it is used as evidences. Yet, there is divergng view of Ulama on its validity of using it as hujjah. There are several Ulama who accept its validity as hujjah and who reject it. Meanwhile, the validity of sadd al-dhari>’ah is considered valid if it receives a legitimation from the authoritative government along with its sanctions for who violates.